Prawidłowości w zagospodarowaniu terenów poprzemysłowych. Przykład Poznania - Mizgajski, Andrzej; Machnicki, Michał (My University, 2009)
The study problem addressed in this paper concerns a sequence in which the post-industrial areas that emerged in relation to the system transformation were managed. The cognitive purpose of the study performed was to diagnose the use of post-industrial land identified in Poznañ and general regularities in the management of those areas as well as in the degree to which they were degraded. Based on an analysis of topographic maps and field research it was possible to identify trends in the management of post-industrial areas in periods 1993–1998 and 1998–2006, and the degree of their degradation in connection with their position in the functional and spatial structure of the city. The newly presented results were documented in quantitative categories of accelerated pace of change in the city spatial structure over the current decade. It is a result, and simultaneously an indicator, of an accelerated economic development and growing society’s affluence, which undoubtedly stems from Poland’s joining the EU economic area. The highest dynamics of growth was observed for the residential function, where the surface area rose tenfold in post-industrial areas. In absolute figures, the largest growth in surface area was noted for trade and service functions, which emerged in areas previously used for manufacturing or warehousing and storage. The consequence of functional changes was a significant decrease in industrial emissions and a clear improvement of air quality indices within the city. Nonetheless, the process of eliminating areas with an industrial or warehousing and storage functions from the city centre has not yet been completed, which shows that the city authorities should more actively stimulate translocation or elimination of such areas.
Regularities in the management of post-industrial areas. Example of Poznań
Keywords: Post-industrial areas; system transformation; Poznań; spatial management; tereny poprzemysłowe; transformacja ustrojowa; Poznań; zagospodarowanie przestrzenne